The von Hippel-Lindau Tumor Suppressor Gene Inhibits Hepatocyte Growth Factor/Scatter Factor-Induced Invasion and Branching Morphogenesis in Renal Carcinoma Cells - Koochekpour, Shahriar (American Society for Microbiology, 1999)
Loss of function in the von Hippel-Lindau (VHL) tumor suppressor gene occurs in familial and most sporadic renal cell carcinomas (RCCs). VHL has been linked to the regulation of cell cycle cessation (G(0)) and to control of expression of various mRNAs such as for vascular endothelial growth factor. RCC cells express the Met receptor tyrosine kinase, and Met mediates invasion and branching morphogenesis in many cell types in response to hepatocyte growth factor/scatter factor (HGF/SF). We examined the HGF/SF responsiveness of RCC cells containing endogenous mutated (mut) forms of the VHL protein (VHL-negative RCC) with that of isogenic cells expressing exogenous wild-type (wt) VHL (VHL-positive RCC). We found that VHL-negative 786-0 and UOK-101 RCC cells were highly invasive through growth factor-reduced (GFR) Matrigel-coated filters and exhibited an extensive branching morphogenesis phenotype in response to HGF/SF in the three-dimensional (3D) GFR Matrigel cultures. In contrast, the phenotypes of A498 VHL-negative RCC cells were weaker, and isogenic RCC cells ectopically expressing wt VHL did not respond at all. We found that all VHL-negative RCC cells expressed reduced levels of tissue inhibitor of metalloproteinase 2 (TIMP-2) relative to the wt VHL-positive cells, implicating VHL in the regulation of this molecule. However, consistent with the more invasive phenotype of the 786-0 and UOK-101 VHL-negative RCC cells, the levels of TIMP-1 and TIMP-2 were reduced and levels of the matrix metalloproteinases 2 and 9 were elevated compared to the noninvasive VHL-positive RCC cells. Moreover, recombinant TIMPs completely blocked HGF/SF-mediated branching morphogenesis, while neutralizing antibodies to the TIMPs stimulated HGF/SF-mediated invasion in vitro. Thus, the loss of the VHL tumor suppressor gene is central to changes that control tissue invasiveness, and a more invasive phenotype requires additional genetic changes seen in some but not all RCC lines. These studies also demonstrate a synergy between the loss of VHL function and Met signaling.